2016
DOI: 10.2147/opth.s115547
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of automatic spectral domain optical coherence tomography for glaucoma mass screening

Abstract: PurposeTo perform a preliminary evaluation of the applicability of automatic spectral domain optical coherence tomography (ASD-OCT) for glaucoma mass screening in a population-based setting.MethodsInformation using ASD-OCT (thicknesses of the macular retinal nerve fiber layer [mRNFL], disc retinal nerve fiber layer [dRNFL], ganglion cell layer [GCL] + inner plexiform layer [IPL]; GCL+, and ganglion cell complex [GCL + IPL + RNFL; GCL++]) was obtained from 245 eyes of 123 glaucomatous subjects and 1,454 eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
(20 reference statements)
1
13
0
1
Order By: Relevance
“…All these macula-specific features make this region prone to oedema. 32 Thinning of GCL has been observed in both primary open angle glaucoma 33 and DR with or without DME. The disruption of the BRB in DR involves numerous factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these macula-specific features make this region prone to oedema. 32 Thinning of GCL has been observed in both primary open angle glaucoma 33 and DR with or without DME. The disruption of the BRB in DR involves numerous factors.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been reported that changes in the inner retinal layers, including ganglion cell layer (GCL) and inner plexiform layer (IPL), are indicators of severity of retinal ischemia secondary to different etiologies. 32 Thinning of GCL has been observed in both primary open angle glaucoma 33 and DR with or without DME. 12,34 Therefore, possible correlations between GCLT and the parameters representing retinal ischemia and macular oedema were studied.…”
Section: Discussionmentioning
confidence: 99%
“…In glaucoma, an ideal screening test has remained elusive, but OCT purportedly offers several advantages over previously suggested screening methods such as intraocular pressure, cup‐disc ratio and screening visual field paradigms . But results for the use of OCT as a screening device in glaucoma have been mixed . As described above, there are no clear diagnostic ‘signs’ of glaucoma identifiable using OCT.…”
Section: Future Directionsmentioning
confidence: 99%
“…From a pool of 10,000 patients and assuming a glaucoma prevalence of 3.4 per cent, 340 will have glaucoma. Assuming 80 per cent sensitivity and 95 per cent specificity (the average across four studies), 272 cases and 9,177 normal patients will be correctly identified. Yet, 483 normal patients will be falsely identified as glaucoma and 68 cases with glaucoma will be missed.…”
Section: Future Directionsmentioning
confidence: 99%
“…Si bien es cierto que, aunque esta medida ha demostrado ser fiable y con alto poder discriminatorio entre pacientes sanos y con glaucoma, 76;77 con valores de área bajo la curva ROC de 0,83 para discriminar entre sanos y pacientes con glaucoma avanzado 77 lo que no resulta especialmente interesante en detección precoz. Además, la gran mayoría de los trabajos publicados en la literatura se refieren a la tecnología OCT-SD [133][134][135][136][137][138] y se desconoce su aplicabilidad y precisión diagnóstica de la tecnología OCT-TD al tener una menor resolución axial en la medida de esta capa. 135 Por este motivo, en la presente tesis doctoral se optó sólo por el estudio de la CFN con ambas tecnologías (OCT-TD y OCT-SD), y porque en atención primaria prácticamente no se cuenta con SD-OCT.…”
Section: Pruebas Estructuralesunclassified